2015
DOI: 10.5897/ajps2013.1111
|View full text |Cite
|
Sign up to set email alerts
|

Coffee leaf damaging insects occurrence in the forest coffee ecosystem of southwestern Ethiopia

Abstract: Insects are diverse and abundant in forest ecosystems, but poorly documented in afromontane rainforests in Southwestern Ethiopia where Coffea arabica L. originated and is distributed worldwide. Therefore, the present study was initiated to study the occurrence of coffee leaf damaging insect pests in the afromontane rainforest of southwestern Ethiopia. Accordingly, surveys on insect pest of coffee were conducted to investigate pest status and; their damaging intensity in three (Yayu, Berhane-kontir and Bonga) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…In contrast, the coffee leaf skeletonizer had very similar infestation levels in the two seasons. While seasonal patterns of the serpentine miner, skeletonizer and free-feeding herbivory have not been described previously, our finding of higher densities of the coffee blotch miner in the wet season matches previous findings (Ababulgu, 2010;Abedeta et al, 2015). These patterns also match previous reports by Lomelí-Flores et al ( 2010) of higher abundances of the coffee leaf miner Leucoptera coffeella during the wet season in Mexico.…”
Section: (D)supporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, the coffee leaf skeletonizer had very similar infestation levels in the two seasons. While seasonal patterns of the serpentine miner, skeletonizer and free-feeding herbivory have not been described previously, our finding of higher densities of the coffee blotch miner in the wet season matches previous findings (Ababulgu, 2010;Abedeta et al, 2015). These patterns also match previous reports by Lomelí-Flores et al ( 2010) of higher abundances of the coffee leaf miner Leucoptera coffeella during the wet season in Mexico.…”
Section: (D)supporting
confidence: 93%
“…The coffee leaf skeletonizer Leucoplema dohertyi (Warren) [family Epiplemidae] has a free‐feeding larva that feeds on the underside of the leaf, and its damage is very distinct as it leaves behind the upper epidermis and veins (Figure 1d). Finally, there are several other free‐feeding insect species that feed on Arabica coffee, including several lepidopterans, slugs and snails (Figure 1e; Abedeta et al, 2015; Crowe, 2004). The coffee berry borer, the main insect pest on coffee berries in coffee growing regions in the world, is not common in this landscape (Mendesil et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…There was no statistically significant difference in the damage of coffee plant by various pests (P>0.05) among studied coffee landraces and across the study sites though the highest severity level was recorded by coffee berry borer, H. hampei, which is the world"s worst coffee pest. Nonetheless, Chemeda et al (2015) reported significance differences in insect pest occurrence between and within forest coffee populations with regard to coffee leaf damaging insects. The following are important classes of pests addressed in the Gedeo Zone.…”
Section: The Diversity Of Insect Pests and The Damage Levelmentioning
confidence: 99%
“…The current study investigated thirteen arthropod coffee pests in Gedeo enset-coffee based agroforestry system but Chemeda et al (2015) identified 12 insect families of five insect orders from afromontane rainforests in Southwestern Ethiopia where C. arabica L. has originated. There was no statistically significant difference in the damage of coffee plant by various pests (P>0.05) among studied coffee landraces and across the study sites though the highest severity level was recorded by coffee berry borer, H. hampei, which is the world"s worst coffee pest.…”
Section: The Diversity Of Insect Pests and The Damage Levelmentioning
confidence: 99%
“…This implies that the highest number of coffee farms was infested by coffee blotch miner as compare to skeletonizer and serpentine. Chemeda et al [3] reported significance differences in insect pest occurrence between and within forest coffee populations with regard to coffee leaf damaging insects. According to Fikadu et al [12] coffee skeletonizer and serpentine leaf miner were found as minor coffee insect pestsat Gedeo zone of Southern Ethiopia.…”
Section: Assessment Of Coffee Leaf Miners (Blotch Miner Skeletonizer ...mentioning
confidence: 99%